2023
DOI: 10.1037/pst0000488
|View full text |Cite
|
Sign up to set email alerts
|

Integrating between-session homework in psychotherapy: A systematic review of immediate in-session and intermediate outcomes.

Abstract: This article reviews the evidence for between-session homework (BSH) in individual psychotherapy. Whereas previous reviews have demonstrated a positive association between-client compliance with BSH and distal treatment outcomes; here, we pay particular attention to therapist behaviors that may promote client engagement with BSH assessed as immediate (in-session) and intermediate (session-to-session) outcomes, and moderators of these effects. For our systematic review, we identified 25 studies with 1,304 clien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…• Homework assignments can cause some clients to feel pressure, anxiety, worsened mood, resistance, and ruptures. The use of structured worksheets (e.g., thought and activity diaries) as homework seems to be particularly difficult for depressed clients, and some clients experienced suicidal thoughts from watching recorded videotapes at home of their own treatment sessions as part of exposure homework (Ryum et al, 2023).…”
Section: Possible Negative Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Homework assignments can cause some clients to feel pressure, anxiety, worsened mood, resistance, and ruptures. The use of structured worksheets (e.g., thought and activity diaries) as homework seems to be particularly difficult for depressed clients, and some clients experienced suicidal thoughts from watching recorded videotapes at home of their own treatment sessions as part of exposure homework (Ryum et al, 2023).…”
Section: Possible Negative Effectsmentioning
confidence: 99%
“…For empathic reflections, Elliott et al (in press) noted that similar results have been found for motivational interviewing across sociocultural dimensions, although most of the research was conducted with Black and Hispanic clients. For between-session homework, Ryum et al (2023) found that the impact of client characteristics was mostly negligible, but added that most research has been conducted with Western clients. For cognitive-experiential dreamwork, Spangler and Sim (2023) noted similar benefit for university clients in the United States and Taiwan.…”
Section: Diversity Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, authors were united in positing the need to customize BSH to the individual client in distinct ways that align closely with existing guidelines and research (e.g., Kazantzis et al, 2005;Ryum et al, 2023c), which is remarkable given the heterogenous nature of the clinical material presented. For example, the case studies demonstrate how a specific BSH task, at a given point in the treatment process, is likely to be most effective when it is informed by the case conceptualization and hypothesis about maintaining factors, build upon material that transpires within the session and clients' needs and strengths (and context), is presented with a credible rationale aligned with treatment goals, and when possible barriers and obstacles to client engagement are discussed.…”
Section: The Process Of Integrating Bshmentioning
confidence: 99%
“…In the “Introduction” to this issue of the Journal of Clinical Psychology: In Session , we summarized some of the strongest research support for adopting between‐session homework (BSH) into clinical work with clients in psychotherapy (Ryum et al, 2023a; see also recent reviews in Kazantzis et al, 2016; Ryum et al, 2023b, 2023c), and argued that it may be considered a common (Kazantzis & Ronan, 2006) or transtheoretical method (Ryum & Kazantzis, 2023) that is highly relevant for clinical training and practice across treatment approaches. We emphasized that the process of facilitating client engagement with specific tasks relies on productive in‐session dynamics and therapist skills and competence in selecting, planning, and reviewing BSH, to ensures a skillful integration.…”
Section: Introductionmentioning
confidence: 99%